DESIGNING â€œe-PoPROTEXTâ€ TO TEACH STUDENTS OF MADRASAH TSANAWIYAH ON PROCEDURE TEXT - Nur, Dewi Shohifah; Ikhsanudin, Ikhsanudin; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to design Microsoft PowerPoint as teaching media in learning procedure text. The method of this research is development research using ADDIE instructional design (Analyzing, Designing, Developing, Implementing, and Evaluating) as the phases in designing e-PoPROTEXT. e-PoPROTEXT is a Microsoft PowerPoint or electronic presentation containing materials about the topic that is talking about procedure text. e-PoPROTEXT provides three menus as the main features. The menus are the main menu, about and help. Each menu presents different content related tothe topic with full color, animation, and audio. The data were calculated using pre-test and post-test and also assessment rubric of expert validation. Based on the result of the data computation, it was obtained that the studentsâ€™ score of post-test (92.37) was higher than studentsâ€™ score of pretest (72.24). The effect size was 1.6 which showed that it was categorized strong effect. Therefore, e-PoPROTEXT is effective in learning procedure text. The assessment rubric of e-PoPROTEXT result is the e-PoProtext as feasible to be used as teaching multimedia. In conclusion, the use of e-PoPROTEXT effective in teaching procedure text.Â Keyword: Microsoft PowerPoint, e-PoPROTEXT, ADDIE Instructional Design